Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus Terhadap Kemiskinan Dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening di Jawa Tengah Tahun 2019-2022 - Rahmasari, Adelia Putri; Dewi, Maya Widyana; Ningsih, Suhesti (Jurnal Akuntansi dan Pajak, 2024)
This research aims to determine the effect of local revenue, general allocation funds and special allocation funds on poverty with economic growth as an intervening variable in central java province. Poverty is the dependent variable of this research, and local revenue, general allocation funds, and special allocation funds are the independent variables of this research. This study involved 35 districts/cities in central java province from 2019 to 2022, and used a purposive sampling method. This research uses secondary data from the APBD Realization Report from the Financial Audit Agency and the Central Java Province Central Statistics Agency. Path analysis was performed using IBM SPSS Statistics. Results from research. The research results show that local revenue, general allocation funds, special allocation funds influence poverty and economic growth, while regional revenue, general allocation funds and special allocation funds influence poverty through economic growth. However, local revenue, general allocation funds, special allocation funds do not affect poverty through economic growth. Keywords : special allocation funds, general allocation funds, poverty, local revenue, economic growth